Identification Of The Meaning And Form Of Malay Decorative Varieties In The Mabmi Langkat Building - Nazriah, Putri; Mirsa, Rinaldi; Muliana, Erna (Rumoh Journal of Architecture, 2025)
Langkat Regency, as one of the regions with strong Malay cultural roots in North Sumatra, shows its cultural existence through various aspects, including building architecture. One of the prominent buildings that represents Malay culture in Langkat is the Indonesian Malay Cultural Council (MABMI) Building. This building was established as a center for Malay cultural and customary activities, so it is inherently expected to display visual characteristics that reflect Malay identity and values. This building is an important representation of Malay cultural identity in the region. This study aims to identify the symbolic meaning and visual form of Malay decorative motifs applied to the Indonesian Malay Cultural Council (MABMI) Building in Langkat Regency, North Sumatra. The method used is a descriptive qualitative approach with data collection techniques through direct observation, visual documentation, and interviews with local cultural sources. The results of the study show that the decorative motifs used are dominated by floral motifs such as bamboo shoots, tendrils, and lotus flowers, as well as geometric ornaments that reflect the principles of balance and harmony in Malay culture. The meaning contained in the motif reflects religious values, morality, and the harmonious relationship between humans and nature and the Creator. In conclusion, the decorative motifs in the MABMI Langkat Building not only function as aesthetic elements, but also as a medium for preserving Malay cultural values ​​that are full of philosophical meaning.